BRAC's contribution to gross domestic product of Bangladesh - Mallick, Debdulal (Research and Evaluation Division, Brac, 2019)
This paper estimates the contribution of BRAC programmes to the gross domestic product (GDP) of Bangladesh. BRAC's contribution to GDP of Bangladesh has been divided into four components. These are 1) Value added in BRAC as an organization in a given year, 2) Incremental value added in linked sectors due to input supply to BRAC in a given year, 3) Incremental value added in linked sectors attributed to loans disbursed by BRAC in a given year, and 4) Incremental value added in linked sectors attributed to nonfinancial development inputs (skill training, non-formal primary education, and health services) in a given year. BRAC contributed Tk. 8,215.3 million, Tk. 10,479.1 million, Tk. 13,558 million and Tk. 17,770.3 million to GDP ofBangladesh in 1995, 1996, 1997 and 1998 respectively. In 1995 BRAC's share to GDP was 0.7%, which increased to 1.15% in 1998. This shows that output of BRAC increased faster than GDP of Bangladesh. During the period output of BRAC increased, on average, at 29.1% annually. But estimating the contribution of education intervention was not possible due to lack of information on the sectoral wage differential of the BRAC graduates and those without any education. Therefore, the total output of BRAC is not fully captured in the present study.